Simultaneous Design of Optimal Shape and Local Cubic Material Characteristics - CZUBACKI, Radosław; GANGHOFFER, Jean-Francois; LEWIŃSKI, Tomasz (Engineering Transactions, 2017)
This paper deals with the minimum compliance problem of the femur bone made of a non-homogeneous elastic material with cubic symmetry. The elastic moduli as well as the trajectories of anisotropy directions are design variables. The isoperimetric condition determines the value of the cost of the design expressed as the integral of the trace of the Hooke’s tensor. The optimum design is found for a selected design domain and a single load case. The optimal cubic material characteristics are reflected by the properties of the underlying microstructure. Admissible microstructures are reconstructed, thus delivering a deeper insight into the optimum design. The obtained microstructures are second- rank laminates composed of an isotropic material and voids. To eliminate the degeneracy of the design at least three load cases should be considered.